EMOTIONAL INTELLIGENCE DAN PERILAKU KEPEMIMPINAN PENDIDIKAN ISLAM - Fauzi, Ahmad (JURNAL AL-TANZIM, 2018)
Sociologically, emotional intelligence is an important part of this study to build leadership social behavior in the management of Islamic education, so that it can color the dynamics of leadership so far and can increase individual loyalty in the organization. Therefore, a leader in mobilizing, motivating and inspiring individuals in the organization requires an emotional approach as a model to awaken individuals in improving their performance culture. Thus the role and actions of leadership in various systems of Islamic education are essentially actualization processes of internalization values inherent in his personality, especially regarding (emotional intelligence). At the theoretical level, emotional intelligence is an important part in building ideal leadership. Portrait of emotional intelligence-based leadership can give birth to two leadership models, including: a) emotional intelligence-based leadership is seen as more effective, and has a strong influence on individual loyalty in Islamic education - even high and low emotional intelligence also affects the high and low loyalty and performance culture. b) the emotional intelligence of a leader cannot be measured by the level of education, even someone's degree. Therefore, it does not guarantee that someone who has a high position or has a high title has high emotional intelligence.